The Influence of Family Stability on Self‐Control and Adjustment. Issue 7 (2nd November 2012) - Malatras, Jennifer Weil; Israel, Allen C.
<x xml:space="preserve">Abstract</x> Objectives The aim of the present study was to replicate previous evidence for a model in which self‐control mediates the relationship between family stability and internalizing symptoms, and to evaluate a similar model with regard to externalizing problems. Method Participants were 155 female and 134 male undergraduates—mean age of 19.03 years. Participants completed measures of stability in the family of origin (Stability of Activities in the Family Environment), self‐control (Self‐Control scale), current externalizing (Adult Self‐Report), and internalizing problems (Beck Depression Inventory II and Beck Anxiety Inventory). Results Multiple regression analyses largely support the proposed model for both the externalizing and internalizing domains. Conclusions Family stability may foster the development of self‐control and, in turn, lead to positive adjustment.